Pentecostalism, the Prosperity Gospel, and Poverty in Africa - Ijaola, Samson O. (Pentecostalism and Politics in Africa, 2018)
Ijaola argues in this chapter that, notwithstanding the prevalence of the prosperity gospel, the number of people living in poverty has been on the increase in Africa. The chapter uses historical criticism to examine the trajectory and performance of Pentecostalism and the prosperity gospel vis-à-vis the reality of poverty in Africa. It observes a paradigm shift from theology of “claim it and have it” to “work and have it” by faith. Pentecostal preachers in Africa, while striving to mitigate poverty, also encourage business and philanthropic engagements. Ijaola concludes that the promise of the prosperity gospel is yet to be fulfilled in Africa.
paid